NIVELIR TURLARI VA ANIQ NIVELIR N3 NI TEKSHIRISH - G‘afforov, Abdurshid Abdisalim o‘g‘li; Xushvaqtov , Asadbek Saydulla o‘g‘li (Innovative Development in Educational Activities, 2023)
When solving many problems, for example, to describe reliefs on a topographic map, it is necessary to know the absolute height of the location points. For this, leveling works are carried out. That is, the relative height between the points in the place is determined, and the absolute height of other points is calculated for a point whose absolute height is known.